WORKERS’ SALARY ACCOUNTING IN COST OF CIVIL ENGINEERING WORKS - O. S. Goloubova; U. V. Sosnovskaya (Наука и техника)
A normative method for price formation established in civil engineering determines a procedure of cost formation in respect of any work. However, main problems are still pending in spite of introduction of new estimate-normative РСН-2007-base. The paper considers problems concerning inclusion of workers’ salary in the cost of works, tendencies of the 2008-legislation alterations, their effect on growth of work cost.